2009
DOI: 10.4067/s0717-97072009000400005
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability and Kinetic Studies of Cobalt (Ii), Nickel (Ii), Copper (Ii), Cadmium (Ii) and Mercury (Ii) Complexes Derived From N-Salicylidene Schiff Bases

Abstract: The thermal properties of a number of Schiff base metal complexes in nitrogen atmosphere have been investigated by thermogravimetry (TG) and differential thermogravimetry (DTG). The kinetic analyses of the thermal decomposition were studied using the Coats-Redfern and Horowitz-Metzger equations. The obtained kinetic parameters show the kinetic compensation effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…From Figures 9 and 10, it is to be concluded that the thermal dеcomposition of the Cu nano complex generally involves overlapping steps, which together with the great diversity of possible intermediate products. [27,28] 3.9 | Electronic absorption spectra, EAS…”
Section: Thermal Analysismentioning
confidence: 99%
“…From Figures 9 and 10, it is to be concluded that the thermal dеcomposition of the Cu nano complex generally involves overlapping steps, which together with the great diversity of possible intermediate products. [27,28] 3.9 | Electronic absorption spectra, EAS…”
Section: Thermal Analysismentioning
confidence: 99%